LACK OF IN VITRO ANTI--GLUCOSIDASE, ANTI-LIPASE AND IMMUNOMODULATORY ACTIVITIES OF ETHANOL EXTRACT FROM FINGER-ROOT (BOESENBERGIA ROTUNDA L.) RHIZOME (Journal of Pharmaceutical Negative Results, 2022)
Recently, metabolic syndrome is related to development of cardiovascular diseases and diabetes mellitus. In addition, immune cells are plays role in physiological dysfunction associated with obesity and metabolic syndrome. Fingerroot (Boesenbergia rotunda L.) rhizome is commonly applied as food flavoring in Asian cuisines and also applied in traditional medicine to relieve commonly on gastrointestinal symptoms. Several studies had reported that flavonoids and terpenoids contained in fingerroot are exhibits wide range of biological activities and use for obesity treatment. Previously phytochemical screening of methanolic extract from B. rotunda rhizome had demonstrated potent α-glucosidase and pancreatic lipase inhibitors. Due to Thai ethnomedicinal utilizations, traditional medicine is usually use herbs extracted with water or ethanol. Hence, this study was attempted to evaluate α-glucosidase and pancreatic lipase inhibitory activities; and immunomodulatory activity of ethanol extract from fingerroot rhizome (FRE). Total phenolic content (TPC) and total flavonoid content (TFC) were 91.51±0.76 mg of GAE/g and 21.05±1.53 mg of QE/g, respectively. FRE was lack of α-glucosidase and pancreatic lipase inhibitory activities when compared with acarbose (IC50 = 1.11±0.33 mg/ml) and orlistat (IC50 = 0.29±0.08 mg/ml). There was unable to stimulate phagocytosis of neutrophils and interpretated as lack of immunomodulatory activity when compared with lipopolysaccharide (LPS).